Maximising expected value under axiological uncertainty - Riedener, S (2015)
The topic of this thesis is axiological uncertainty – the question of how you should evaluate your options if you are uncertain about which axiology is true. As an answer, I defend Expected Value Maximisation (EVM), the view that one option is better than another if and only if it has the greater expected value across axiologies. More precisely, I explore the axiomatic foundations of this view. I employ results from state-dependent utility theory, extend them in various ways and interpret them accordingly, and thus provide axiomatisations of EVM as a theory of axiological uncertainty. Chapter 1 defends the importance of the problem of axiological uncertainty. Chapter 2 introduces the most basic theorem of this thesis, the Expected Value Theorem. This theorem says that EVM is true if the betterness relation under axiological uncertainty satisfies the von Neumann-Morgenstern axioms and a Pareto condition. I argue that, given certain simplifications and modulo the problem of intertheoretic comparisons, this theorem presents a powerful means to formulate and defend EVM. Chapter 3 then examines the problem of intertheoretic comparisons. I argue that intertheoretic comparisons are generally possible, but that some plausible axiologies may not be comparable in a precise way. The Expected Value Theorem presupposes that all axiologies are comparable in a precise way. So this motivates extending the Expected Value Theorem to make it cover less than fully comparable axiologies. Chapter 4 then examines the concept of a probability distribution over axiologies. In the Expected Value Theorem, this concept figures as a primitive. I argue that we need an account of what it means, and outline and defend an explication for it. Chapter 5 starts to bring together the upshots from the previous three chapters. It extends the Expected Value Theorem by allowing for less than fully comparable axiologies and by dropping the presupposition of probabilities as given primitives. Chapter 6 provides formal appendices.